Primary Sjogren’s Syndrome Associated With Treatment-Resistant Obsessive–Compulsive Disorder - Ong, Lawrence T. C.; Galambos, Gary; Brown, David A. (Frontiers in Psychiatry, 2017)
There is an increasing awareness that autoimmune diseases can present with neuropsychiatric manifestations. We present the case of a 17 year old female requiring psychiatric hospitalisation for obsessive compulsive disorder and major depressive disorder with mixed affective features, who was subsequently diagnosed with primary Sjogren’s syndrome. Treatment with potent immunosuppression resulted in remission of psychiatric illness. Due to a lack of awareness and/or the lack of specific biomarkers, clinicians may not associate psychiatric symptoms with autoimmune disease, including primary Sjogren’s syndrome. This case demonstrates that Sjogren’s syndrome may be a causative or aggravating factor in mental disorders and that autoimmune diseases should be carefully considered in the differential diagnosis of psychiatric illness especially in cases of concurrent physical symptomatology and severity or treatment resistance of psychiatric disease.